The hydrostratigraphic and groundwater flow modeling of Mukah coal mining affected areas - Jubin Aro, Joseph; Ibrahim, Shaharin (2009)

(untitled)
The hydrostratigraphic and groundwater flow information within the vicinity of Mukah Coal field is important to provide a guideline in protecting the groundwater resources. The delineation of the regional aquifer–aquitard framework requires precise evaluation of the hydrostratigraphic controls and temporal patterns of groundwater flow of the study area. Possible natural contaminants include trace elements such as arsenic and selenium, radionuclides such as radon, and high concentrations of commonly occurring dissolved constituents are the possibly wash out together with spillage of removed overburden and eventually enter the groundwater aquifer. The hydrostratigrahic interpretation and the groundwater flow modeling are supported by Lithologic data analysis, wireline logging, resistivity imaging lines, and from the Ground Penetrating radar runs within the study area. The lithologic logs were obtained from 26 drill holes including drill holes for groundwater exploration and drill holes for coal exploration within the study area. A total of 8 Wirelines run for these drill also used to confirm the lithologic logs of the drill holes. Both resistivity imaging (6 runs) and Ground Penetrating Radar (6 runs) methods were used to evaluate further lithological sections of the study area. The study area is dominated by various aquifer systems, which are mostly unconfined. In several localities, this main aquifer has been locally divided into multiple layers by the presence of discontinuous aquitards (with a lateral extent of one to a few kilometers). Generally, the direction of groundwater flow is towards the central part of Mukah Coal Mining area.